FUNCTIONAL OUTCOME AFTER OPEN REDUCTION AND INTERNAL FIXATION (ORIF) OF INTRA-ARTICULAR CALCANEAL FRACTURES â€“ TWO CASE REPORTS - Arsovski, Oliver; Krstevski, Stefan; Hajradinovic, Dino; Ðndonovski, Antonio; Kaftandziev, Igor (Journal of Morphological Sciences; Vol 5 No 3 (2022): JMS, 2022)
Unique and simple parameters have not yet been established according to which we can evaluate the surgical reduction and assume the functional outcomes in calcaneal fractures. The classic radiological Bohlerâ€™s angle is considered a sensitive parameter for assessing the quality of the reduction but not so adequate in the functional outcome assessment. In this paper we report two cases of Open Reduction and Internal Fixation (ORIF) of calcaneal fractures using already established methodology. Patients were treated according to the standard procedure using lateral approach, open reduction and osteosynthesis with anatomic locking plate. Postoperative Bohlerâ€™s angle was measured on postoperative radiographs compared to contralateral healthy leg. Functional outcomes were assessed one year after injury using the American Orthopaedics Foot and Ankle Society (AOFAS) scale.   Case report 1: A 39-year-old man, injured in a traffic accident as a car driver sustained right calcaneal fracture and a fracture of the facial bones suitable for conservative treatment. The preoperative Bohlerâ€™s angle was 15Ëš. Surgery was done on the eleventh day post-injury. Postoperatively Bohlerâ€™s angle was 37Ëš compared to the uninjured leg where it was 32Ëš. The functional outcome one year after the injury was 89 points according to AOFAS scale.  Case report 2 : A 51-year-old woman injured by fall from a height of 1.5 meters sustained an isolated left calcaneal fracture. On the initial radiographs Bohlerâ€™s angle was 13Ëš. Surgery was done on the eighth day post-injury. Bohlerâ€™s angle measured on postoperative radiographs was 29Ëš compared to the uninjured calcaneus - 31Ëš. Superficial wound infection occurred postoperatively, which was managed with local treatment. Functional outcome using AOFAS scale was 91 points. A good reduction was achieved in both presented cases which correlated to good functional outcome at one year after injury. In determining the true value of this radiological parameter as a predictor of functional outcome we suggest studies on large patient samples with extensive analysis of multiple factors that may influence. Keywords : calcaneus, Bohlerâ€™s angle, fracture, outcome.